An Energy Star Physical Vapor Deposition (PVD) Machine - Bushroa, A.R.; Noor Ashiha, A.; Reza, M.; Mohd, H.; Vijay, G.; K, W. (2016)
Physical Vapor Deposition (PVD) Technique is one of the most favourable techniques to deposit thin films in the range of Nano scale. However, the current PVD setup in the market has several deficiencies. The normal size of the PVD is relatively large and this will require larger parts and devices to build the system that contributes to a larger space to locate the equipment. The target used (i.e. The source of the atom to be deposited as a thin film) in the conventional method is normally in the solid form. Target of ceramic, a combination of more than one element, inorganic or powders could not be sputtered using the conventional method due to the unsupportive design of PVD. The conventional PVD for lab-scale usage could be improved by the innovative design of magnetron sputtering that utilizes the concentration of electrons to enhance the plasma ionization. The design highlights the arrangement of magnets to capture and entrap electrons for better ionization rate. This knowledge is transferred to ULVAC (M) Sdn Bhd to be embedded into the conventional lab-scale PVD to enable the sputter of powders. Since sputtering the powder and its mixture is relatively easier and efficient in this PVD system, the technology will enhance innovative and creative formulation of various thin film depositions for different properties. This innovative technology is seen to address issues of industrial related community to find new ideas for improved properties of thin film and its application and to reduce costs.